Hypothalamic POMC deficiency increases circulating adiponectin despite obesity - Hui Yu; Kavaljit H. Chhabra; Zoe Thompson; Graham L. Jones; Sylee Kiran; Gary Shangguan; Malcolm J. Low (Elsevier, 2020)
Objective: The steep rise in the prevalence of obesity and its related metabolic syndrome have become a major worldwide health concerns. Melanocortin peptides from hypothalamic arcuate nucleus (Arc) POMC neurons induce satiety to limit food intake. Consequently, Arc Pomc-deficient mice (ArcPomc−/−) exhibit hyperphagia and obesity. Previous studies demonstrated that the circulating levels of adiponectin, a protein abundantly produced and secreted by fat cells, negatively correlate with obesity in both rodents and humans. However, we found that ArcPomc−/− mice have increased circulating adiponectin levels despite obesity. Therefore, we investigated the physiological function and underlying mechanisms of hypothalamic POMC in regulating systemic adiponectin levels. Methods: Circulating adiponectin was measured in obese ArcPomc−/− mice at ages 4-52 weeks. To determine whether increased adiponectin was a direct result of ArcPomc deficiency or a secondary effect of obesity, we examined plasma adiponectin levels in calorie-restricted mice with or without a history of obesity and in ArcPomc−/− mice before and after genetic restoration of Pomc expression in the hypothalamus. To delineate the mechanisms causing increased adiponectin in ArcPomc−/− mice, we determined sympathetic outflow to adipose tissue by assessing epinephrine, norepinephrine, and tyrosine hydroxylase protein levels and measured the circulating adiponectin in the mice after acute norepinephrine or propranolol treatments. In addition, adiponectin mRNA and protein levels were measured in discrete adipose tissue depots to ascertain which fat depots contributed the most to the high level of adiponectin in the ArcPomc−/− mice. Finally, we generated compound Adiopoq−/−:ArcPomc−/− mice and compared their growth, body composition, and glucose homeostasis to the individual knockout mouse strains and their wild-type controls. Results: Obese ArcPomc−/− female mice had unexpectedly increased plasma adiponectin compared to wild-type siblings at all ages greater than 8 weeks. Despite chronic calorie restriction to achieve normal body weights, higher adiponectin levels persisted in the ArcPomc−/− female mice. Genetic restoration of Pomc expression in the Arc or acute treatment of the ArcPomc−/− female mice with melanotan II reduced adiponectin levels to control littermate values. The ArcPomc−/− mice had defective thermogenesis and decreased epinephrine, norepinephrine, and tyrosine hydroxylase protein levels in their fat pads, indicating reduced sympathetic outflow to adipose tissue. Injections of norepinephrine into the ArcPomc−/− female mice reduced circulating adiponectin levels, whereas injections of propranolol significantly increased adiponectin levels. Despite the beneficial effects of adiponectin on metabolism, the deletion of adiponectin alleles in the ArcPomc−/− mice did not exacerbate their metabolic abnormalities. Conclusion: In summary, to the best of our knowledge, this study provides the first evidence that despite obesity, the ArcPomc−/− mouse model has high circulating adiponectin levels, which demonstrated that increased fat mass is not necessarily correlated with hypoadiponectinemia. Our investigation also found a previously unknown physiological pathway connecting POMC neurons via the sympathetic nervous system to circulating adiponectin, thereby shedding light on the biological regulation of adiponectin. Keywords: Adiponectin, POMC, Sympathetic nervous system, Melanocortin system